EVOH material with high hydroxyl content and preparation method and application thereof

By combining polyvinyl acetate and other organic epoxy compounds for alcoholylation, EVOH materials with high hydroxyl content are prepared, which solves the problem of difficulty in synthesizing EVOH with high vinyl alcohol content in the prior art, and achieves high barrier, high temperature resistance and versatility of the material.

CN115651112BActive Publication Date: 2025-03-14BEIJING UNIV OF CHEM TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210970369.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-13
Publication Date
2025-03-14
Estimated Expiration
2042-08-13

AI Technical Summary

Technical Problem

The prior art is difficult to synthesize ethylene vinyl alcohol copolymers (EVOH) with a molar content of more than 45% of vinyl alcohol, and the lack of suitable catalysts limits the development of high barrier packaging materials.

Method used

By combining polyvinyl acetate, ethylene/methacrylic acid copolymer, etc. with organic epoxy compounds or oligomers containing epoxy bonds, and alcoholylation reaction is carried out to prepare EVOH materials with high hydroxyl content.

Benefits of technology

The obtained high hydroxyl content EVOH material has a high melting point, high temperature resistance, good water solubility and oil repellency, and is suitable for film materials of oil production agents and optical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115651112B_ABST
    Figure CN115651112B_ABST
Patent Text Reader

Abstract

EVOH material with high hydroxyl content, preparation method and application, hydroxyl molar content of 16-98%, is a random or block organic polymer material with a molecular weight of 1000-100000000 g / mol containing hydroxyl, carboxyl, ester, ether bond or polyethylene chain in accordance with general formula (1). In the presence of organic alcohol metal solution and organic epoxy compound solution, polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer or PAM are dissolved in alcohol for alcoholysis, and the prepared EVOH material has high temperature resistance, non-toxicity, excellent water barrier performance, moisture barrier performance, gas barrier performance, etc., easy processing, easy recovery and other characteristics, is the first choice of barrier packaging materials, film materials, etc., and is also particularly suitable for high temperature oil displacement agents for tertiary oil recovery. The method of the present invention is simple, low in cost, good in effect, low in energy consumption, pollution-free, and no carbon dioxide is generated during the production process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyolefin resins and polyolefin elastomers or polyolefin plastic materials and elastic materials, and in particular relates to EVOH materials with high hydroxyl content and a preparation method and application of the EVOH materials with high hydroxyl content. Background Art

[0002] With the rapid development of production technology, there are a large number of food and agricultural products to be exported in my country, most of which are rich in protein, fat and water. Due to the poor quality of packaging materials, they are prone to deterioration in the hot and humid seasons of spring and summer every year, resulting in a large amount of waste. In terms of export, they cannot meet international packaging standards and affect the country's reputation.

[0003] Therefore, it is extremely urgent to develop and synthesize packaging materials with high barrier properties. Due to its own characteristics, EVOH is non-toxic, has good water barrier, moisture barrier, gas barrier, easy processing, recycling, and no pollution, and has become the first choice for barrier packaging materials.

[0004] The current method for synthesizing EVA is high temperature and high pressure free radical polymerization, but the VA content is no more than 40wt% (15.9mol%), while the high barrier material EVOH requires a vinyl alcohol molar content of more than 45%.

[0005] Currently, there is no suitable catalyst for synthesizing EVA with a VA molar content of more than 45%. EVOH was first produced by the DuPont Company in the United States in the 1950s through copolymerization and alcoholysis of ethylene and vinyl acetate, but it has been discontinued.

[0006] In 1972, Japan's Kuraray Company built its first EVOH production line, and in 1984, Japan's Synthetic Chemical Industry Company built its first EVOH production line. Since then, the two companies have occupied 70% of the EVOH resin market.

[0007] In 2007, the EVOH resin production line of Changchun Petrochemical Company in Taiwan, China was put into operation.

[0008] At present, there is still no report on the production of EVOH resin powder in China.

[0009] So far, the world's main producers of this product are two Japanese companies and Changchun Petrochemical Company in Taiwan, China.

[0010] The present invention unexpectedly finds that when polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or a mixture thereof is subjected to alcoholysis reaction, an appropriate amount of organic epoxy compound or organic oligomer with a molecular weight of 100-50000 g / mol containing epoxy bonds is added, and polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) or a mixture thereof is fully or partially alcoholyzed to obtain an EVOH material with a higher melting point or amorphous, high hydroxyl content, and containing or containing part of vinyl acetate groups, wherein the higher melting point or amorphous is a melting point between 100° C. and 210° C. or has no obvious melting point (with an EVOH material having a higher melting point or amorphous). Figure 1 ), wherein the high hydroxyl content is the hydroxyl molar content in the EVOH material of 10-99%, wherein the non-existence or partial presence of vinyl acetate groups or carboxyl groups is the vinyl acetate group or carboxyl molar content in the EVOH material of 0-90%;

[0011] The invention finds that the prepared EVOH material with a high hydroxyl content of 10-99% is resistant to high temperature and soluble in water, and the aqueous solution of the EVOH material has high viscosity and excellent oil displacement effect, and is an oil recovery agent with excellent performance, and is particularly suitable for tertiary oil recovery. The invention finds that the prepared EVOH material with a high hydroxyl content of 10-99% is resistant to high temperature, has excellent transparency, is easy to process, and is easy to form a film, and is a high-quality membrane material or filter membrane material for optical devices. The invention finds that the prepared EVOH material with a high hydroxyl content of 10-99% is resistant to high temperature, has excellent water absorption performance, and is easy to process, and is a hydrogel material or a high-strength water absorption material with excellent performance. The invention finds that the prepared EVOH material with a high hydroxyl content of 10-99% is an elastomer with excellent performance. Summary of the invention

[0012] One of the purposes of the present invention is to provide an EVOH material with a high hydroxyl content, wherein the EVOH material with a high hydroxyl content has a hydroxyl molar content of 16-98%, a melting point between 100°C and 220°C or no obvious melting point, contains no or part of vinyl acetate groups, and has a vinyl acetate group or carboxyl molar content of 0-90%;

[0013] One of the purposes of the present invention is to provide an EVOH plastic material with a high hydroxyl content, wherein the EVOH material with a high hydroxyl content has a hydroxyl molar content of 16-98%, a melting point between 100°C and 220°C or no obvious melting point, contains no or part of vinyl acetate groups, and has a vinyl acetate group or carboxyl molar content of 0-90%;

[0014] One of the purposes of the present invention is to provide an EVOH elastic material with a high hydroxyl content, wherein the EVOH material with a high hydroxyl content has a hydroxyl molar content of 16-98% in the EVOH material, contains no or part of vinyl acetate groups, and has a vinyl acetate group or a carboxyl molar content of 0-60%;

[0015] One of the purposes of the present invention is to provide an EVOH material with a high hydroxyl content, wherein the EVOH material with a high hydroxyl content is a polymer conforming to the general formula (1); wherein the EVOH material with a high hydroxyl content is a random or block organic polymer with a molecular weight of 1000-100000000 g / mol; wherein the molecular structure of the EVOH material with a high hydroxyl content contains hydroxyl groups, ester groups, ether bonds, carboxyl groups and polyethylene chains or polypropylene chains or other polyolefin chains;

[0016]

[0017] Wherein, x is an integer of 0-10000, y is an integer of 50-6000000, m is an integer of 4-100000, n is an integer of 1-100000, x+y+m+n=55-6210000; wherein, R is H, CH 3 , CH 2 Cl, C 1 -C 5000 Alkyl, C 1 -C 5000 Alkoxy, C 1 -C 5000 Silane group, C 1 -C 5000 Siloxyl groups, C 6 -C 5000 Aryl, C 6 -C 5000 The aryloxy group, C 6 -C 5000 Aralkyl, C 1 -C 5000 The haloalkyl group, C 6 -C 5000 The halogenated aryl, C 1 -C 5000 The hydroxyl-containing alkyl group, C 1 -C 5000An ester-containing alkyl group, wherein R' is H, Me, or C 1 -C 50 Alkyl, C 1 -C 50 Alkoxy, C 1 -C 50 Silane group, C 1 -C 50 Siloxyl groups, C 6 -C 50 Aryl, C 6 -C 50 The aryloxy group, C 6 -C 50 Aralkyl, C 1 -C 50 The haloalkyl group, C 6 -C 50 wherein R" is H, Me or C 1 -C 30 Alkyl, C 1 -C 30 Alkoxy, C 1 -C 30 Silane group, C 1 -C 30 Siloxyl groups, C 6 -C 30 Aryl, C 6 -C 30 The aryloxy group, C 6 -C 30 Aralkyl, C 1 -C 30 haloalkyl or C 6 -C 30 wherein q is 0 or an integer from 1 to 30;

[0018] One of the purposes of the present invention is to provide a preparation method and application of an EVOH material with a high hydroxyl content, the preparation method comprising the following steps:

[0019] (1) adding one or more monomers selected from the group consisting of ethylene, propylene, butylene, butadiene, pentadiene, styrene, octene, vinyl acetate, propylene acetate, butylene acetate, MMA, EMMA or acrylamide, and a solvent to a reaction kettle, stirring, adding an initiator, maintaining the pressure at 0.1-30 MPa, raising the temperature to 10-200° C., and polymerizing for 1-20 hours, to cause free radical or coordination homopolymerization or copolymerization, and obtaining a homopolymer or copolymer polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) or a mixture thereof; wherein the initiator is an azo initiator. The invention relates to an organic initiator such as AIBN, a peroxide initiator such as BPO, a redox initiator, a ZN catalyst, a non-metallocene catalyst or a metallocene catalyst, wherein the ZN catalyst is a ZN titanium catalyst, a ZN chromium catalyst or a ZN vanadium catalyst, wherein the non-metallocene catalyst is a late transition metal organic catalyst, an early transition metal organic catalyst or a non-metallocene catalyst containing a strong electron-withdrawing group in the ligand, wherein the metallocene catalyst is a single metallocene catalyst, a double metallocene catalyst, a bridged metallocene catalyst, a CGC catalyst, a phosphine metallocene catalyst or a metallocene catalyst containing a strong electron-withdrawing group in the ligand, wherein the conditions for the free radical homopolymerization or copolymerization are a pressure of 0.1-30 MPa, a polymerization temperature of 10-200° C., and a polymerization time of 1-20 hours, wherein the solvent is C 1 -C 12 organic alcohol such as methanol, ethanol, propanol or butanol, etc.; wherein the mass ratio of the solvent to the monomer is 100:(5-70).

[0020] (2) dissolving polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) or a mixture thereof in an organic alcohol at 0-40° C., wherein the dissolution temperature is 20-160° C.; after dissolution, cooling to 10-60° C.; wherein the organic alcohol is C 1 -C 10The alcohol is preferably methanol, ethanol, propanol, ethylene glycol, propylene glycol, glycerol, isopropanol, butanol, isobutanol, amyl alcohol, isopentanol, hexanol, isohexanol, heptanol, isoheptanol, octanol, isooctyl alcohol, decanol, isodecanol or a mixture thereof; wherein the mass ratio of polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) or a mixture thereof to an organic alcohol is (2-55): 100, wherein the mixture is two or more of polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) etc. mixed in any mass ratio.

[0021] (3) adding an organic alcohol metal solution, an organic epoxy compound or C to (2) continuously, multiple times or once at 10-60°C. 3 -C 50 A monobasic or polybasic organic acid, wherein the organic epoxy compound is C 2 -C 10 An organic compound containing epoxy bonds or an organic oligomer containing epoxy bonds with a molecular weight of 100-50000 g / mol; wherein the C 3 -C 50 The monobasic or polybasic organic acid is C 3 -C 50 Saturated fatty acids, C 3 -C 50 unsaturated fatty acid or aromatic organic acid; at 30-150° C., stirred, reacted for 4-20 hours; wherein the organic alcohol metal solution is an organic alcohol alkali metal solution or an organic alcohol alkaline earth metal solution, wherein the organic alcohol alkali metal solution or the organic alcohol alkaline earth metal solution is a saturated methanol solution of sodium hydroxide, a saturated methanol solution of potassium hydroxide, a saturated methanol solution of calcium hydroxide, a saturated ethanol solution of sodium hydroxide, a saturated ethanol solution of potassium hydroxide, a saturated ethanol solution of calcium hydroxide, a methanol solution of sodium hydroxide, a saturated butanol solution of sodium hydroxide or a saturated propanol solution of potassium hydroxide or a mixed solution thereof; wherein the organic epoxy compound solution is an organic epoxy compound dissolved in C 1 -C 10wherein the organic alcohol is selected from methanol, ethanol, ethylene glycol, propanol, butanol, pentanol, hexanol, heptanol, octanol or decanol or a mixture thereof; wherein the reaction temperature is selected from 30-150° C., and if the reaction temperature is close to the boiling point of the solvent organic alcohol, a reflux technique is used; wherein the mass volume ratio of polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) or a mixture thereof to the organic alcohol metal solution is 10 g:(0.1-30 mL); wherein the polyvinyl acetate (PVAc) or EVA or ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) or a mixture thereof to an organic epoxy compound or C 3 -C 50 The mass ratio of the monobasic or polybasic organic acid is 10:(0.01-9.0).

[0022] (4) Filter (3) at 0-60°C and use C 1 -C 6 The organic alcohol is washed 1-5 times, and vacuum dried at 30-60° C. to obtain an EVOH material with a high hydroxyl content; wherein the C 1 -C 6 The organic alcohol is methanol, ethanol, propanol, ethylene glycol, propylene glycol, butanol, pentanol or hexanol or a mixture thereof; wherein the mass volume ratio of the polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) or a mixture thereof to the organic alcohol is 100 (g): (30-500 mL).

[0023] (5) adding additives to the product obtained in (4) at 0-60° C., extruding and granulating by a screw extruder, and cooling to obtain EVOH pellets with a high hydroxyl content; wherein the heating section temperature of the screw extruder is 150-260° C., the screw speed is 35-75 r / min, and the feeding rate is 3-50 kg / h; wherein the screw extruder is a twin-screw extruder, a three-screw extruder or a single-screw extruder; wherein the additive is an antibacterial agent, an antioxidant, a colorant, a nucleating agent or a wetting agent, and the mass ratio of EVOH to the additive is 10 0: (0.01-30); wherein the additive is but not limited to benzoate compounds, curcumin, γ-cyclodextrin, biphenyl diester, p-methoxybenzoic acid, 4-methylphthalic acid, 4-sulfophthalic acid, tert-butylhydroquinone, BHA (butylated hydroxyanisole), tea polyphenols, propyl gallate (PG), vegetable oil, animal oil, mineral oil, mineral white oil, PAO, fluoropolyethers, 4-sulfophthalic acid, carnauba wax, beeswax, tocopherol, talc, paraffin, magnesium stearate or microcrystalline cellulose or a mixture thereof.

[0024] The EVOH material with high hydroxyl content prepared by the technology of the present invention is an organic polymer material with a molecular weight of 1000-100000000 g / mol; the technology of the present invention can prepare EVOH material with very high molecular weight, and the molecular weight even exceeds the test range of all existing test instruments.

[0025] The EVOH material with high hydroxyl content, preparation method and application are characterized in that: the polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or polyacrylamide (PAM) or a mixture thereof is subjected to alcoholysis reaction to obtain an EVOH material with a molecular weight higher than the molecular weight of the original polymer.

[0026] The EVOH material of the present invention has hydroxyl or carboxyl groups at both ends of the side group or chain; the EVOH material with high hydroxyl content of the present invention has ester groups at both ends of the side group or chain; the EVOH material with high hydroxyl content has a hydroxyl molar content of 16-99% in the EVOH material molecular chain; each monomer unit in the EVOH material molecular chain contains a side group, wherein the side group is a hydroxyl group, an ester group, a carboxyl group, an ether bond, H or R"; the EVOH material has a vinyl acetate group or carboxyl molar content of 0-90% in the EVOH material; wherein the hydroxyl molar content of 16-99% is the molar percentage of all side groups occupied by hydroxyl groups; wherein the side groups are hydroxyl groups, ester groups, carboxyl groups, ether bonds, H or R" and the like; wherein the material does not contain or contains part of vinyl acetate groups, wherein the vinyl acetate group or carboxyl molar content is 0-90%, which is the molar percentage of all side groups occupied by vinyl acetate groups or carboxyl groups.

[0027] The EVOH material prepared by the technology of the present invention has a relatively high melting point or amorphous EVOH material with a high hydroxyl content, and contains no or some vinyl acetate groups, wherein the relatively high melting point or amorphous EVOH material has a melting point of 100°C-210°C or has no obvious melting point, wherein the high hydroxyl content means that the molar content of hydroxyl groups in the EVOH material is 16-99%, and the molar content of vinyl acetate groups or carboxyl groups in the EVOH material is 0-90%. The EVOH material prepared by the present invention has excellent properties such as high temperature resistance and high barrier properties, is non-toxic and pollution-free, has excellent water barrier properties, moisture barrier properties, gas barrier properties, etc., is easy to process, and is easy to recycle, and is the first choice for barrier packaging materials.

[0028] The EVOH material with a hydroxyl molar content of 16-99% prepared by the technology of the present invention is resistant to high temperatures and soluble in water. The aqueous solution of the EVOH material has high viscosity and excellent oil displacement effect. It is an oil recovery agent with excellent performance, and is particularly suitable for tertiary oil recovery.

[0029] The EVOH material with a hydroxyl molar content of 16-99% prepared by the technology of the present invention is resistant to high temperatures, has excellent transparency, is easy to process, is easy to form a film, has stable performance, and is particularly suitable for the application of various optical films, filter films or other films.

[0030] The invention finds that the prepared EVOH material with a hydroxyl molar content of 16-99% or a carboxyl molar content of 0-90% is resistant to high temperature, has excellent water absorption performance, is easy to process, and is an excellent hydrogel material or a high-strength water-absorbing material.

[0031] The EVOH material with a hydroxyl molar content of 16-99% prepared by the technology of the present invention is an elastomeric material with excellent performance and easy processing.

[0032] The EVOH material with high hydroxyl content, preparation method and application are characterized in that: before the alcoholysis reaction of polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or polyacrylamide (PAM) or a mixture thereof, it is necessary to dissolve in an organic alcohol at a dissolution temperature of 20-160° C. and stir; wherein the organic alcohol is C 1 -C 10 The alcohol is preferably methanol, ethanol, propanol, ethylene glycol, propylene glycol, glycerol, isopropanol, butanol, isobutanol, amyl alcohol, isopentanol, hexanol, isohexanol, heptanol, isoheptanol, octanol, isooctyl alcohol, decanol, isodecanol or a mixture thereof; wherein the mass ratio of polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) to the organic alcohol is (2-55):100.

[0033] The EVOH material with high hydroxyl content and its preparation method and application are characterized in that: the polyvinyl acetate (PVAc) or EVA or ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) or a mixture thereof is subjected to alcoholysis reaction, and an organic epoxy compound or C is added continuously, multiple times or once during the reaction process. 3 -C 50 The monobasic or polybasic organic acid is maintained at a temperature of 30-150° C., stirred, and reacted for 4-20 hours; wherein the organic epoxy compound is C 2 -C 10 An organic compound containing one or more epoxy bonds, preferably ethylene oxide, propylene oxide, butylene oxide, epichlorohydrin, 4-methoxyphenyl glycidyl ether, 1,4-butanediol diglycidyl ether or 4,4'-methylenebis(N,N-diglycidyl aniline) or a mixture thereof; wherein the organic epoxy compound is an organic oligomer containing an epoxy bond and having a molecular weight of 100-50000 g / mol, preferably epoxy soybean oil, phenyl glycidyl ether-formaldehyde copolymer, etc.; wherein the C 2 -C 50 The monobasic or polybasic organic acid is C 2 -C 50 Saturated fatty acids, C 2 -C 50 Unsaturated fatty acids or C 6-C 50 The aromatic organic acid is selected from acetic acid, oxalic acid, succinic acid, phthalic acid, 4-methylphthalic acid, terephthalic acid, 4-sulfophthalic acid or pyromellitic acid, etc.; wherein the polyvinyl acetate (PVAc) or EVA or ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) or a mixture thereof and an organic epoxy compound or C 3 -C 50 The mass ratio of the monobasic or polybasic organic acid is 10:(0.01-9.0).

[0034] The EVOH material with high hydroxyl content, preparation method and application are characterized in that: the polyvinyl acetate (PVAc) or EVA or ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) or a mixture thereof is subjected to alcoholysis reaction, and an organic alcohol metal solution is added continuously or multiple times or once during the reaction process, the temperature is maintained at 30-150° C., stirred, and reacted for 4-20 hours; wherein the organic alcohol metal solution is a saturated methanol solution of sodium hydroxide, a saturated methanol solution of potassium hydroxide, , a saturated methanol solution of calcium hydroxide, a saturated ethanol solution of sodium hydroxide, a saturated ethanol solution of potassium hydroxide, a saturated ethanol solution of calcium hydroxide, a methanol solution of sodium hydroxide, a saturated butanol solution of sodium hydroxide or a saturated propanol solution of potassium hydroxide or a mixed solution thereof, etc.; wherein the mass volume ratio of polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) or a mixture thereof to the organic alcohol metal solution is 10g:(0.1-30mL).

[0035] The EVOH material with high hydroxyl content, preparation method and application are characterized in that: the polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) or a mixture thereof is subjected to the above alcoholysis reaction, filtered at 0-60°C, and C 1 -C 6The organic alcohol is washed 1-5 times and dried to obtain an EVOH material with a high hydroxyl content; wherein the mass volume ratio of the polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or propylene / ethylene / vinyl ester copolymer or higher olefin / propylene / ethylene / vinyl ester copolymer or polyacrylamide (PAM) or a mixture thereof to the organic alcohol is 100 (g): (30-500 mL).

[0036] The EVOH material with a high hydroxyl content, preparation method and application are characterized in that: the EVOH material with a high hydroxyl content is a polymer conforming to the general formula (1); wherein the polymer conforming to the general formula (1) is a random or block organic polymer with a molecular weight of 300-580000000 g / mol; wherein the EVOH material product contains hydroxyl groups, ester groups, ether bonds, carboxyl groups, polyethylene chains or polypropylene chains or other polyolefin chains;

[0037]

[0038] Wherein, x is an integer of 0-10000, y is an integer of 50-6000000, m is an integer of 4-100000, n is an integer of 4-100000, x+y+m+n=55-6210000; wherein, R is H, CH 3 , CH 2 Cl, C 1 -C 5000 Alkyl, C 1 -C 5000 Alkoxy, C 1 -C 5000 Silane group, C 1 -C 5000 Siloxyl groups, C 6 -C 5000 Aryl, C 6 -C 5000 The aryloxy group, C 6 -C 5000 Aralkyl, C 1 -C 5000 The haloalkyl group, C 6 -C 5000 The halogenated aryl, C 1 -C 5000 The hydroxyl-containing alkyl group, C 1 -C 5000 An ester-containing alkyl group, wherein R' is H, Me, or C 1 -C 50 Alkyl, C 1 -C 50Alkoxy, C 1 -C 50 Silane group, C 1 -C 50 Siloxyl groups, C 6 -C 50 Aryl, C 6 -C 50 The aryloxy group, C 6 -C 50 Aralkyl, C 1 -C 50 The haloalkyl group, C 6 -C 50 wherein R" is H, Me or C 1 -C 30 Alkyl, C 1 -C 30 Alkoxy, C 1 -C 30 Silane group, C 1 -C 30 Siloxyl groups, C 6 -C 30 Aryl, C 6 -C 30 The aryloxy group, C 6 -C 30 Aralkyl, C 1 -C 30 haloalkyl or C 6 -C 30 wherein q is 0 or an integer from 1 to 30.

[0039] The EVOH material with high hydroxyl content, preparation method and application are characterized in that: the EVOH material of general formula (1) is a product obtained by alcoholysis of polyvinyl acetate (PVAc), EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or polyacrylamide (PAM) or a mixture thereof prepared by free radical homopolymerization or copolymerization of monomers such as ethylene, propylene, vinyl acetate, propylene acetate, butylene acetate, MMA, EMMA or acrylamide; wherein the initiator used for the free radical homopolymerization or copolymerization is an azo organic initiator such as AIBN, a peroxide compound initiator such as BPO or a redox initiator, wherein the conditions for the free radical homopolymerization or copolymerization are a pressure of 0.1-30 MPa, a polymerization temperature of 10-200° C., a polymerization time of 1-20 hours, and a solvent of C 1 -C 12 organic alcohol such as methanol, ethanol, propanol or butanol, etc.; wherein the mass ratio of the solvent to the monomer is 100:(5-70).

[0040] The main effects of the present invention are as follows: the EVOH material with a high hydroxyl content prepared by the present invention is an organic polymer material with a molecular weight of 300-580000000 g / mol; the present invention can prepare an EVOH material with a very high molecular weight, and the molecular weight even exceeds the test range of all existing test instruments; the EVOH material prepared by the present invention has a relatively high melting point or an amorphous EVOH material with a high hydroxyl content and containing no or part of vinyl acetate groups, wherein the relatively high melting point or amorphous EVOH material has a melting point of 100°C-210°C or has no obvious melting point (attached Figure 1 ), wherein the high hydroxyl content is the hydroxyl molar content of 16-99% in the EVOH material, and the EVOH material containing no or part of vinyl acetate groups is the vinyl acetate group or carboxyl molar content of 0-90% in the EVOH material. The EVOH material prepared by the present invention has excellent properties such as high temperature resistance and high barrier properties, is non-toxic and pollution-free, has excellent water barrier properties, moisture barrier properties, gas barrier properties, etc., is easy to process, and is easy to recycle. It is the first choice for barrier packaging materials, etc.; the EVOH material prepared by the present invention is resistant to high temperatures and soluble in water. The aqueous solution of the EVOH material has high viscosity and excellent oil displacement effect. It is an excellent oil recovery agent, especially suitable for tertiary oil recovery. The present invention finds that the high hydroxyl content EVOH material prepared with a hydroxyl or carboxyl molar content of 10-99% is resistant to high temperatures, has excellent water absorption performance, and is easy to process. It is an excellent hydrogel material or high-strength water-absorbing material; the EVOH material with a hydroxyl molar content of 10-99% prepared by the technology of the present invention is resistant to high temperatures, has excellent transparency, is easy to process, is easy to form a film, has stable performance, and is especially suitable for the application of various optical films and other films. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is the DSC result of EVOH.

[0042] The present invention is further described below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the following embodiments. DETAILED DESCRIPTION

[0043] Example 1

[0044] Add 5 kg of vinyl acetate and 10 L of methanol into a 30 L reactor at 30 °C, stir, add 50 g of AIBN, raise the temperature to 60 °C, fill with ethylene to a pressure of 8 MPa, react for 3 hours, and obtain 4.8 kg of PVAc with a molecular weight of 230,000;

[0045] Example 2

[0046] Add 5 kg of vinyl acetate (VA) and 10 L of methanol into a 30 L reactor at 30 °C, stir, add 50 g of AIBN, raise the temperature to 60 °C, fill with ethylene to a pressure of 1.2 MPa, react for 3.5 hours, and obtain 5.1 kg of EVA with a molecular weight of 250,000;

[0047] Example 3

[0048] Add 5kg of MMA and 10L of methanol into a 30L reactor at 30°C, stir, add 50g of BPO, heat to 85°C, charge with ethylene to a pressure of 1.5MPa, react for 8.5 hours, and obtain 3.5kg of EMMA with a molecular weight of 65,000;

[0049] Example 4

[0050] Add 5kg of MA and 10L of cyclohexane into a 30L reactor at 20℃, stir, add 50g of CGC-Ti, raise the temperature to 65℃, fill with ethylene to a pressure of 2.5MPa, react for 4.5 hours, and obtain 1.5kg of EMA with a molecular weight of 45,000;

[0051] Referring to the synthesis conditions and synthesis technology of PVAc, EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or polyacrylamide (PAM) etc. are prepared.

[0052] PVAc, EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or polyacrylamide (PAM) etc. prepared by Examples 1-4 can also be used in Examples 5-24. PVAc, EVA, ethylene / MMA copolymer (EMMA) or ethylene / MA copolymer (EMA) or ethylene / methacrylic acid copolymer (EMAA) or polyacrylamide (PAM) can also be purchased from the market for use in Examples 5-24.

[0053] Example 5

[0054] Add 10 g of PVAc to a 250 mL reaction bottle at 25°C, add 100 mL of methanol, stir, reflux, and heat to 60°C until PVAc dissolves; cool to 40°C, add 10 mL of sodium methoxide solution and 10 mL of epichlorohydrin methanol solution (2.2 g of epichlorohydrin is dissolved in methanol to make a 10 mL solution) to the reaction bottle in succession, stir, and react for 9 hours; filter at 40°C, wash twice with methanol (60 mL of methanol each time), and vacuum dry at 50°C to obtain 6.3 g of EVOH with a hydroxyl molar content of 80%; add 0.063 g of curcumin and 0.035 g of propyl gallate at 30°C, extrude by twin-screw at 230°C, and pelletize to obtain 6.3 g of EVOH pellets with a hydroxyl molar content of 80% and a viscosity-average molecular weight of 340,000.

[0055] Example 6

[0056] At 30°C, 10 g of PVAc was added to a 300 mL reaction bottle, and 100 mL of methanol was added. The mixture was stirred and refluxed, and the temperature was raised to 60°C until the PVAc was dissolved. The mixture was cooled to 40°C, and 10 mL of sodium methoxide and 10 mL of epichlorohydrin methanol solution (6.3 g of epichlorohydrin was dissolved in methanol to prepare a 10 mL solution) were added to the reaction bottle in succession. The mixture was stirred and reacted for 8 hours. The mixture was filtered at 40°C, washed with methanol twice (60 mL of methanol each time), and vacuum dried at 50°C to obtain 6.5 g of EVOH with a hydroxyl molar content of 40%. 0.065 g of p-methoxybenzoic acid and 0.035 g of butylated hydroxytoluene were added at 45°C, and twin-screw extrusion and pelletization were performed at 235°C to obtain 6.4 g of EVOH pellets with a hydroxyl molar content of 40% and a viscosity-average molecular weight of 9.56 million.

[0057] Example 7

[0058] Add 10 g of PVAc into a 250 mL reaction bottle at 25°C, add 100 mL of methanol, stir, reflux, and heat to 60°C until PVAc dissolves; cool to 40°C, add 8 mL of sodium methoxide solution and 10 mL of epichlorohydrin methanol solution (1.0 g of epichlorohydrin is dissolved in methanol to make a 10 mL solution) into the reaction bottle in succession, stir, and react for 7 hours; filter at 40°C, wash twice with ethanol (50 mL of ethanol each time), and vacuum dry at 50°C to obtain 6.9 g of EVOH with a hydroxyl molar content of 96%; add 0.065 g of γ-cyclodextrin and 0.025 g of tea polyphenols at 45°C, extrude by twin-screw at 235°C, and pelletize to obtain 6.8 g of EVOH pellets with a hydroxyl molar content of 96% and a viscosity-average molecular weight of 3.51 million.

[0059] Example 8

[0060] At 25°C, 10 g of EVA was added to a 250 mL reaction bottle, 100 mL of butanol was added, stirred, refluxed, and the temperature was raised to 90°C until the EVA was dissolved; the temperature was lowered to 50°C, 8 mL of sodium methoxide solution and 10 mL of epichlorohydrin methanol solution (3.0 g of epichlorohydrin was dissolved in methanol to prepare a 10 mL solution) were added to the reaction bottle in 5 equal portions, stirred, and reacted for 7 hours; at 30°C, filtered, washed with ethanol twice (50 mL of ethanol each time), and vacuum dried at 60°C to obtain 6.5 g of EVOH with a hydroxyl molar content of 15.6%; 0.065 g of γ-cyclodextrin and 0.007 g of tea polyphenols were added at 45°C, twin-screw extruded at 245°C, pelletized, and 6.6 g of EVOH pellets with a hydroxyl molar content of 15.6% and a viscosity-average molecular weight of 520,000 were obtained.

[0061] Example 9

[0062] At 25°C, 10 g of EMMA was added to a 250 mL reaction bottle, 100 mL of butanol was added, stirred, and the temperature was raised to 90°C until EMMA dissolved; the temperature was lowered to 50°C, 8 mL of sodium methoxide solution and 10 mL of epichlorohydrin and 4-methylphthalic acid methanol solution (3.0 g of epichlorohydrin and 0.9 g of 4-methylphthalic acid were dissolved in methanol to prepare a 10 mL solution) were added to the reaction bottle in 5 equal portions, stirred, and reacted for 12 hours; at 30°C, filtered, washed with ethanol twice (50 mL of ethanol each time), and vacuum dried at 60°C to obtain 6.6 g of EVOH with a hydroxyl molar content of 30%; 0.065 g of biphenyl diester and 0.007 g of tea polyphenols were added at 45°C, twin-screw extrusion was performed at 255°C, and pelletization was performed to obtain 6.6 g of EVOH pellets with a hydroxyl molar content of 30% and a viscosity-average molecular weight of 68,000.

[0063] Example 10

[0064] At 25°C, 10 g of PVAc was added to a 250 mL reaction bottle, and 100 mL of methanol was added. The mixture was stirred and refluxed, and the temperature was raised to 60°C until the PVAc was dissolved. The temperature was lowered to 40°C, and 8 mL of sodium methoxide solution and 10 mL of epichlorohydrin methanol solution (4.3 g of epichlorohydrin was dissolved in methanol to prepare a 10 mL solution) were added to the reaction bottle in succession. The mixture was stirred and reacted for 7 hours. The mixture was filtered at 40°C, washed with ethanol twice (50 mL of ethanol each time), and vacuum dried at 50°C to obtain 6.1 g of EVOH with a hydroxyl molar content of 61%. 0.015 g of p-methoxybenzoic acid and 0.03 g of tea polyphenols were added at 45°C, and twin-screw extrusion and pelletization were performed at 255°C to obtain 6.1 g of EVOH pellets with a hydroxyl molar content of 61% and a viscosity-average molecular weight of 350,000.

[0065] Embodiment 11

[0066] Add 10 g of PVAc into a 250 mL reaction bottle at 20°C, add 100 mL of methanol, stir, reflux, and heat to 60°C until PVAc dissolves; cool to 40°C, add 8 mL of sodium methoxide solution and 10 mL of epichlorohydrin methanol solution (2.3 g of epichlorohydrin is dissolved in methanol to make a 10 mL solution) into the reaction bottle in succession, stir, and react for 7 hours; filter at 40°C, wash twice with ethanol (50 mL of ethanol each time), and vacuum dry at 50°C to obtain 7.0 g of EVOH with a hydroxyl molar content of 75%; add 0.02 g of p-methoxybenzoic acid and 0.02 g of tea polyphenols at 25°C, extrude by twin-screw at 225°C, and pelletize to obtain 7.0 g of EVOH pellets with a hydroxyl molar content of 75% and a viscosity-average molecular weight of 360,000.

[0067] Example 12

[0068] At 20°C, 10 g of PVAc was added to a 250 mL reaction bottle, and 100 mL of methanol was added. The mixture was stirred and refluxed, and the temperature was raised to 60°C until the PVAc was dissolved. The temperature was lowered to 40°C, and 20 mL of sodium methoxide solution and 10 mL of oxalic acid methanol solution (5.1 g of oxalic acid was dissolved in methanol to prepare a 10 mL solution) were added to the reaction bottle in succession, stirred, and reacted for 7 hours. The mixture was filtered at 40°C, washed with ethanol twice (50 mL of ethanol each time), and vacuum dried at 50°C to obtain 5.9 g of EVOH with a hydroxyl molar content of 53%. 0.02 g of p-methoxybenzoic acid and 0.02 g of butylated hydroxytoluene were added at 25°C, and twin-screw extrusion was performed at 225°C. The mixture was pelletized to obtain 5.8 g of EVOH pellets with a hydroxyl molar content of 53% and a viscosity-average molecular weight of 310,000.

[0069] Embodiment 13

[0070] Add 10 g of PVAc into a 250 mL reaction bottle at 20°C, add 100 mL of methanol, stir, reflux, and heat to 60°C until PVAc dissolves; cool to 40°C, add 15 mL of sodium methoxide solution and 10 mL of propylene oxide methanol solution (5.5 g of propylene oxide is dissolved in methanol to make a 10 mL solution) into the reaction bottle continuously, stir, and react for 7 hours; filter at 40°C, wash twice with methanol (50 mL of methanol each time), and vacuum dry at 50°C to obtain 7.8 g of EVOH with a hydroxyl molar content of 48%; add 0.04 g of benzoate compound and 0.04 g of butylated hydroxytoluene at 25°C, twin-screw extrusion at 225°C, pelletize, and obtain 7.8 g of EVOH pellets with a hydroxyl molar content of 48% and a viscosity-average molecular weight of 150,000.

[0071] Embodiment 14

[0072] At 20°C, 10 g of PVAc was added to a 250 mL reaction bottle, and 100 mL of methanol was added. The mixture was stirred, refluxed, and heated to 60°C until the PVAc was dissolved. The mixture was cooled to 40°C, and 10 mL of sodium methoxide solution and 10 mL of epoxidized soybean oil methanol solution (7.5 g of epoxidized soybean oil was dissolved in methanol to prepare a 10 mL solution) were added to the reaction bottle in 10 equal portions, stirred, and reacted for 10 hours. The mixture was filtered at 40°C, washed with methanol twice (50 mL of methanol each time), and vacuum dried at 50°C to obtain 8.5 g of EVOH with a hydroxyl molar content of 50%. 0.04 g of p-methoxybenzoic acid and 0.055 g of butylated hydroxytoluene were added at 25°C, and twin-screw extrusion and pelletization were performed at 215°C to obtain 8.5 g of EVOH pellets with a hydroxyl molar content of 50% and a viscosity-average molecular weight of 180,000.

[0073] Embodiment 15

[0074] At 30°C, 10 g of PVAc was added to a 300 mL reaction bottle, 100 mL of methanol was added, stirred, refluxed, and the temperature was raised to 60°C until the PVAc was dissolved; the temperature was lowered to 40°C, 20 mL of sodium methoxide solution and 10 mL of epichlorohydrin methanol solution (7.5 g of epichlorohydrin was dissolved in methanol to prepare a 10 mL solution) were added to the reaction bottle continuously, stirred, and reacted for 16 hours; at 40°C, filtered, washed with methanol 4 times (60 mL of methanol each time), and vacuum dried at 50°C to obtain 6.1 g of EVOH with a hydroxyl molar content of 36%; 0.032 g of p-methoxybenzoic acid, 0.02 g of 4-sulfophthalic acid, and 0.05 g of dibutylhydroxytoluene were added at 20°C, twin-screw extruded at 215°C, pelletized, and 6.1 g of EVOH pellets with a hydroxyl molar content of 36% were obtained, and the molecular weight was not measured by the viscosity method.

[0075] Example 16

[0076] At 20°C, 10 g of PVAc was added to a 250 mL reaction bottle, 100 mL of methanol was added, stirred, refluxed, and heated to 60°C until the PVAc was dissolved; the temperature was lowered to 40°C, 15 mL of potassium methoxide solution and 10 mL of epoxidized soybean oil methanol solution (7.5 g of epoxidized soybean oil was dissolved in methanol to prepare a 10 mL solution) were added to the reaction bottle in 10 equal portions, stirred, and reacted for 12 hours; at 40°C, filtered, washed with methanol twice (50 mL of methanol each time), and vacuum dried at 50°C to obtain 6.2 g of EVOH with a hydroxyl molar content of 49%; 0.032 g of 4-sulfophthalic acid and 0.05 g of tert-butylhydroquinone were added at 20°C, twin-screw extruded at 215°C, pelletized, and 6.2 g of EVOH pellets with a hydroxyl molar content of 49% and a viscosity-average molecular weight of 170,000 were obtained.

[0077] Embodiment 17

[0078] At 20°C, 10 g of PVAc was added to a 250 mL reaction bottle, 100 mL of ethanol was added, stirred, refluxed, and the temperature was raised to 60°C until the PVAc was dissolved; the temperature was lowered to 40°C, 15 mL of sodium ethoxide solution and 10 mL of 4-methylphthalic acid ethanol solution (4.3 g of 4-methylphthalic acid was dissolved in ethanol to prepare a 10 mL solution) were added to the reaction bottle continuously, stirred, and reacted for 10 hours; at 40°C, filtered, washed with ethanol twice (50 mL of ethanol each time), and vacuum dried at 50°C to obtain 6.1 g of EVOH with a hydroxyl molar content of 72%; 0.035 g of p-methoxybenzoic acid and 0.05 g of tert-butylhydroquinone were added at 30°C, twin-screw extrusion was performed at 215°C, and pelletization was performed to obtain 6.1 g of EVOH pellets with a hydroxyl molar content of 72% and a viscosity-average molecular weight of 350,000.

[0079] Embodiment 18

[0080] At 20°C, 9 g of PVAc and 1 g of EVA were added to a 250 mL reaction bottle, and 60 mL of ethanol and 40 mL of butanol were added, stirred, and the temperature was raised to 60°C until PVAc and EVA were dissolved; the temperature was lowered to 40°C, 15 mL of sodium ethanol solution and 10 mL of epichlorohydrin ethanol solution (3.3 g of epichlorohydrin was dissolved in ethanol to prepare a 10 mL solution) were added to the reaction bottle continuously, stirred, and reacted for 10 hours; at 40°C, filtered, washed with ethanol twice (50 mL of ethanol each time), and vacuum dried at 50°C to obtain 6.5 g of EVOH with a hydroxyl molar content of 65%; 0.035 g of p-methoxybenzoic acid and 0.05 g of tert-butylhydroquinone were added at 30°C, twin-screw extrusion was performed at 220°C, and pelletization was performed to obtain 6.5 g of EVOH pellets with a hydroxyl molar content of 65% and a viscosity-average molecular weight of 450,000.

[0081] Embodiment 19

[0082] At 20°C, 1kg of PVAc was added to a 20L reactor, and 10L of methanol was added. The mixture was stirred, refluxed, and heated to 60°C until the PVAc was dissolved. The mixture was cooled to 40°C, and 1.5L of sodium methoxide solution and 1L of epichlorohydrin methanol solution (230g of epichlorohydrin was dissolved in methanol to prepare a 1L solution) were added to the reaction flask in succession. The mixture was stirred and reacted for 10 hours. The mixture was filtered at 40°C, washed with ethanol twice (5L of ethanol each time), and vacuum dried at 50°C to obtain 0.61kg of EVOH with a hydroxyl molar content of 79%. 1.5g of p-methoxybenzoic acid and 1.35g of tert-butylhydroquinone were added at 30°C, and twin-screw extrusion and pelletization were performed at 210°C to obtain 0.62kg of EVOH pellets with a hydroxyl molar content of 79% and a viscosity-average molecular weight of 551.3 million.

[0083] Embodiment 20

[0084] At 25°C, 100 kg of PVAc was added to a 2000 L reactor, and 1500 L of methanol was added. The mixture was stirred, refluxed, and heated to 60°C until the PVAc was dissolved. The mixture was cooled to 40°C, and 150 L of a saturated sodium methoxide solution and 100 L of an epichlorohydrin methanol solution (23 kg of epichlorohydrin was dissolved in methanol to prepare a 100 L solution) were continuously added to the reaction bottle, stirred, and reacted for 10 hours. The mixture was filtered at 40°C, washed twice with ethanol (500 L of ethanol each time), and vacuum dried at 50°C to obtain 61.3 kg of EVOH with a hydroxyl molar content of 80%. 180 g of p-methoxybenzoic acid and 185 g of tert-butylhydroquinone were added at 30°C, and twin-screw extrusion and pelletization were performed at 220°C to obtain 61.5 kg of EVOH pellets with a hydroxyl molar content of 80% and a viscosity-average molecular weight of 48 million.

[0085] Embodiment 21

[0086] At 20°C, 8 g of PVAc and 2 g of ethylene / 1-octene-7-carboxylic acid methyl ester copolymer (comonomer insertion amount of 1.3%) were added to a 250 mL reaction bottle, 100 mL of butanol was added, stirred, refluxed, and the temperature was raised to 100°C until the polymer was dissolved; the temperature was lowered to 55°C, 12 mL of sodium ethoxide solution and 8 mL of epichlorohydrin ethanol solution (2.8 g of epichlorohydrin was dissolved in ethanol to prepare 8 mL of solution) were continuously added to the reaction bottle, stirred, and reacted for 11 hours; at 40°C, filtered, washed with ethanol twice (50 mL of ethanol each time), and vacuum dried at 50°C to obtain EVOH with a hydroxyl molar content of 51%. 6.3 g; add 0.02 g of microcrystalline cellulose, 0.016 g of p-methoxybenzoic acid, and 0.015 g of tert-butylhydroquinone at 30°C, extrude with a twin screw at 220°C, and cut into pellets to obtain 6.3 g of EVOH pellets with a hydroxyl molar content of 51% and a viscosity-average molecular weight of 410,000.

[0087] Embodiment 22

[0088] At 20°C, 5 g of PVAc, 8.5 g of EVA and 1.5 g of propylene / 1-decene-9-carboxylic acid methyl ester copolymer (comonomer insertion amount of 0.91%) were added to a 250 mL reaction bottle, 100 mL of butanol was added, stirred, refluxed, and the temperature was raised to 100°C until the polymer was dissolved; the temperature was lowered to 55°C, 12 mL of sodium ethoxide solution and 10 mL of epichlorohydrin and 4-sulfophthalic acid ethanol solution (2.3 g of epichlorohydrin and 1.1 g of 4-sulfophthalic acid were dissolved in ethanol to prepare a 10 mL solution) were continuously added to the reaction bottle, stirred, and reacted for 11 hours; at 40°C, filtered, washed with ethanol twice (50 mL of ethanol each time), and vacuum dried at 50°C to obtain EVOH with a hydroxyl molar content of 38%. 6.0 g; add 0.035 g of p-methoxybenzoic acid and 0.025 g of tert-butylhydroquinone at 30°C, extrude with a twin screw at 220°C, cut into pellets, and obtain 6.0 g of EVOH pellets with a hydroxyl molar content of 38% and a viscosity-average molecular weight of 460,000.

[0089] Embodiment 23

[0090] At 25°C, 200kg PVAc was added to a 1000L reactor, and 300L methanol was added. The mixture was stirred, refluxed, and heated to 60°C until the PVAc was dissolved. The mixture was cooled to 40°C, and 28L of a saturated sodium methoxide solution and 15L of an epichlorohydrin methanol solution (4.6kg of epichlorohydrin was dissolved in methanol to prepare a 15L solution) were continuously added to the reaction bottle, stirred, and reacted for 10 hours. The mixture was filtered at 40°C, washed twice with ethanol (75L of ethanol each time), and vacuum dried at 55°C to obtain 121kg of EVOH with a hydroxyl molar content of 78.9%. 484g of p-methoxybenzoic acid, 480g of tert-butylhydroquinone, and 480g of magnesium stearate were added at 30°C, and twin-screw extrusion was performed at 225°C. The mixture was pelletized to obtain 122kg of EVOH pellets with a hydroxyl molar content of 78.9% and a viscosity-average molecular weight of 65.1 million.

[0091] Embodiment 24

[0092] At 20°C, 10 g of PAM was added to a 250 mL reaction bottle, and 150 mL of ethylene glycol was added. The mixture was stirred, refluxed, and heated to 100°C until the polymer was dissolved. The mixture was cooled to 55°C, and 12 mL of sodium ethoxide solution and 8 mL of epichlorohydrin ethanol solution (2.8 g of epichlorohydrin was dissolved in ethanol to prepare 8 mL of solution) were added to the reaction bottle in succession. The mixture was stirred and reacted for 11 hours. The mixture was filtered at 40°C, washed with ethanol twice (50 mL of ethanol each time), and vacuum dried at 50°C to obtain 8.1 g of EVOH with a carboxyl molar content of 81%. 0.01 g of p-methoxybenzoic acid, 0.015 g of tert-butylhydroquinone, and 0.020 g of palm wax were added at 30°C, and twin-screw extrusion was performed at 220°C. The mixture was pelletized to obtain 8.1 g of EVOH pellets with a hydroxyl molar content of 81% and a viscosity-average molecular weight of 121 million.

[0093] Embodiment 25

[0094] 9 g of PVAc and 1 g of EVA were added to a 250 mL reaction bottle at 20°C, 100 mL of methanol was added, stirred, refluxed, and the temperature was raised to 60°C; 10 mL of potassium methoxide solution and 10 mL of epichlorohydrin methanol solution (3 ml of epichlorohydrin was dissolved in methanol to prepare a 10 mL solution) were added to the reaction bottle in 10 equal portions, 10 mL of 4-sulfophthalic acid methanol solution (0.5 g of 4-sulfophthalic acid was dissolved in 10 mL of methanol to prepare a 10 mL solution) was added to the reaction bottle in 10 equal portions, stirred, and reacted for 10 hours; the methanol was removed in a vacuum at 40°C, washed twice with ethanol (50 mL of ethanol each time), and then washed twice with water (50 mL of water each time), and dried in a vacuum at 50°C to obtain 6.2 g of EVOH elastomer with a hydroxyl molar content of 46% and a viscosity-average molecular weight of 650,000.

Claims

1. A method for preparing an EVOH material having a high hydroxyl content, characterized in that: The following steps are involved: (1) Add one or more monomers of ethylene, propylene, butylene, butadiene, vinyl acetate, propylene acetate, butylene acetate, MMA, EMMA or acrylamide and a solvent into a reaction kettle, stir, add an initiator, maintain the pressure at 0.1-30 MPa, raise the temperature to 10-200° C., and polymerize for 1-20 hours to produce a free radical or coordination homopolymerization or copolymerization to obtain a polymer product; wherein the initiator is an azo organic initiator, a peroxide compound initiator, a redox initiator, a ZN catalyst, a non-metallocene catalyst or a metallocene catalyst, and the solvent is C1-C 12 An organic alcohol; wherein the mass ratio of the solvent to the monomer is 100:(5-70); (2) dissolving the polymer product in an organic alcohol at 0-40°C, wherein the dissolution temperature is 20-160°C; after dissolution, cooling to 10-60°C; wherein the organic alcohol is C1-C 10 wherein the mass ratio of the polymerization product to the organic alcohol is (2-55):100; (3) performing alcoholysis reaction at 10-60° C., adding an organic alcohol metal solution, an organic epoxy compound or a C3-C 50 A monobasic or polybasic organic acid, wherein the organic epoxy compound is C2-C 10 An organic compound containing one or more epoxy bonds or an organic oligomer containing one or more epoxy bonds with a molecular weight of 100-50000 g / mol; wherein the C3-C 50 The monobasic or polybasic organic acid is C3-C 50 Saturated fatty acids, C3-C 50 unsaturated fatty acid or aromatic organic acid; at 30-150° C., stirred, reacted for 4-20 hours; wherein the organic alcohol metal solution is an organic alcohol alkali metal solution or an organic alcohol alkaline earth metal solution, wherein the organic alcohol alkali metal solution or the organic alcohol alkaline earth metal solution is a saturated methanol solution of sodium hydroxide, a saturated methanol solution of potassium hydroxide, a saturated methanol solution of calcium hydroxide, a saturated ethanol solution of sodium hydroxide, a saturated ethanol solution of potassium hydroxide, a saturated ethanol solution of calcium hydroxide, a methanol solution of sodium hydroxide, a saturated butanol solution of sodium hydroxide or a saturated propanol solution of potassium hydroxide or a mixed solution thereof; wherein the organic epoxy compound solution is an organic epoxy compound dissolved in C1-C 10 wherein the organic alcohol is selected from methanol, ethanol, ethylene glycol, propanol, butanol, pentanol, hexanol, heptanol, octanol or decanol or a mixture thereof; wherein the mass volume ratio of the polymer product to the organic alcohol metal solution is 10 g: (0.1-30 mL); wherein the polymer product is mixed with an organic epoxy compound or a C3-C 50 The mass ratio of the monobasic or polybasic organic acid is 10:(0.01-9.0); (4) filtering the product obtained in (3) at 0-60° C., washing with a C1-C6 organic alcohol for 1-5 times, and vacuum drying at 30-60° C. to obtain an EVOH material with a high hydroxyl content; wherein the C1-C6 organic alcohol is methanol, ethanol, propanol, ethylene glycol, propylene glycol, butanol, pentanol or hexanol or a mixture thereof; wherein the mass volume ratio of the polymer product to the organic alcohol is 100 g: (30-500 mL); (5) adding additives to the product obtained in (4) at 0-60° C., extruding and granulating by a screw extruder, and cooling to obtain EVOH pellets with a high hydroxyl content; wherein the temperature of the heating section of the screw extruder is 150-260° C.; wherein the additive is an antibacterial agent, an antioxidant, a colorant, a nucleating agent or a wetting agent, and the mass ratio of EVOH to the additive is 100:(0.01-30); wherein the additive is a benzoate compound, curcumin, γ-cyclodextrin, biphenyl diester, p-methoxybenzoic acid, tert-butylhydroquinone, butylated hydroxyanisole, tea polyphenols, propyl gallate, vegetable oil, animal oil, mineral oil, mineral white oil, PAO, fluoropolyether, 4-sulfophthalic acid, carnauba wax, beeswax, tocopherol, talc, paraffin, magnesium stearate, microcrystalline cellulose or a mixture thereof; Wherein, each monomer unit in the molecular chain of the EVOH material with a high hydroxyl content contains a side group, wherein the molar content of hydroxyl groups in the EVOH material with a high hydroxyl content is 16-99%, which is the molar percentage of hydroxyl groups in all side groups; wherein the side group is a hydroxyl group, an ester group, an ether bond or R"; Where R" is H, Me or C1-C 30 Alkyl, C1-C 30 Alkoxy, C1-C 30 Silane group, C1-C 30 Siloxyl groups, C6-C 30 Aryl, C6-C 30 Aryloxy, C6-C 30 Arylalkyl, C1-C 30 haloalkyl or C6-C 30 A halogenated aryl group; Wherein, the EVOH material with a high hydroxyl content is a polymer conforming to the general formula (1); wherein, the EVOH material with a high hydroxyl content is a random polymer or a block polymer with a molecular weight of 1000-10000000 g / mol; wherein, the EVOH material product with a high hydroxyl content mainly contains hydroxyl groups, and also contains ester groups, ether bonds, carboxyl groups, polyethylene chains or polypropylene chains; Wherein, x is an integer of 0-10000, y is an integer of 50-6000000, m is an integer of 4-100000, n is an integer of 1-100000, x+y+m+n=55-6210000; Where R is H, CH3, CH2Cl, C1-C 5000 Alkyl, C1-C 5000 Alkoxy, C1-C 5000 Silane group, C1-C 5000 Siloxy, C6-C 5000 Aryl, C6-C 5000 Aryloxy, C6-C 5000 Arylalkyl, C1-C 5000 Halogenated alkyl, C6-C 5000 The halogenated aryl group, C1-C 5000 A hydroxyl-containing alkyl group, C1-C 5000 An ester-containing alkyl group, wherein R' is H, Me, or C1-C 50 Alkyl, C1-C 50 Alkoxy, C1-C 50 Silane group, C1-C 50 Siloxy, C6-C 50 Aryl, C6-C 50 Aryloxy, C6-C 50 Arylalkyl, C1-C 50 Halogenated alkyl, C6-C 50 wherein R" is H, Me or C1-C 30 Alkyl, C1-C 30 Alkoxy, C1-C 30 Silane group, C1-C 30 Siloxy, C6-C 30 Aryl, C6-C 30 Aryloxy, C6-C 30 Arylalkyl, C1-C 30 haloalkyl or C6-C 30 wherein q is 0 or an integer from 1 to 30.

2. The method for preparing the EVOH material with high hydroxyl content according to claim 1, characterized in that: in, The additives are 4-methylphthalic acid and butylated hydroxytoluene.

3. EVOH material with high hydroxyl content, prepared by the preparation method described in claim 1 or 2.

4. The use of the EVOH material with high hydroxyl content according to claim 3, characterized in that: As barrier packaging materials, oil recovery agents, membrane materials for optical devices, filter membrane materials, hydrogel materials, high-strength water-absorbing materials or elastomers.

Citation Information

Patent Citations

  • Vinyl alcohol series polymer

    CN101955561A

  • Preparation method of high-fluoride polytetrafluoroethylene-contained resin

    CN102585079A

  • Modified ethylene vinyl alcohol copolymer and method for the production thereof

    CN1464883A

  • Vinyl alcohol-based polymer containing amino group in side chain

    TW201905005A